Removal of Cadmium from aqueous solution using agriculture waste as biosorbent / Abdul Halim Razak ... [et al.] - Razak, Abdul Halim; Sapuan, Muhammad Amirul; Bahrum, Muhammad Asri; Ismail, Rodziah; Mohd Tahir, Mohd Pozi; Ishak, Ahmad Razali (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
The use of agriculture waste for the removal of different pollutants including heavy metals has proved to be efficient. This research intentions was to investigate the feasibility of selected agriculture waste (Rubber wood Sawdust- RWSD, Banana Peel- BP, Mangosteen Peel- MP) in removal of Cadmium (Cd) ion from aqueous solution. The factors that could influence the experimental conditions such as pH, amount of adsorbent, initial concentration of Cd, adsorption isotherm and adsorption kinetics of biosorbent were studied. As for RWSD and MP, the adsorption of Cd was more efficient in the basic pH region (pH 9), while BP prefer the neutral pH condition. The adsorption of Cd achieved its dynamic equilibrium within 20 min of contact times for all of the adsorbent. Pseudo second-order model fits better than the pseudo first-order model for adsorption kinetic data and indicates the adsorption process is based on chemisorptions. The equilibrium isotherm data were fitted well to Freundlich isotherm with maximum adsorption capacity of 4.01, 3.16 and 6.90 mg/g for RWSD, BP and MP respectively. From the study, it showed that RWSD, BP and MP have the potential to be utilized as a cost effective and high capability adsorbent for the removal of Cd from aqueous solutions.